Implementation of Environmental Decision Making Tool For Renewable Energy Utilization - Musau, Moses Peter; Abungu, Nicodemus Odero; Wekesa, Cyrus Wabuge (My University, 2017)
Renewable Energy (RE) units especially grid connected Wind and Solar PV which have no rotational inertia are effectively displacing the conventional generators and their rotating systems. This reduces both the cost of generation and environmental effects. However, this has implications on the frequency stability in that frequency dynamics become faster with low inertia. This makes frequency control complex and difficult and thus frequency stability becomes challenging. The frequency deviation should be kept small as Damaging Vibrations (DV) and Under Frequency Load Shedding (UFLS) occur for large deviations in the worst case, leading to total black out. For example, in Kenya, there has been increased penetration of RE especially wind and solar into the grid. On Tuesday 7th June 2016 at 1130Hrs, a nationwide black out hit the country for almost three hours when a monkey tripped at transformer at Gitaru Hydroelectric Power Station, leading to a loss of more than 180MW from the grid. This paper revisits Frequency Stability, UFLS and proposes a Combined Frequency with Renewable Energy Storage Cost (CFS) approach for mitigating frequency instability with RE. A brief outline of the Kenyan Case is also provided.
Keywords: Environmental Decision Making Tool with Renewable Energy (EDMTRE; Midpoint indicators Modified Firefly Algorithm with LevyFlights and Derived Mutation (MFALFDM); Modifed ReCiPe Version 1.3 Model; Structural PathAnalysis (SPA); Renewable Energy (RE)